Development of a Blended English Language Learning Module for Pharmacy Students Using the Whole-Part-Whole (WPW) Model to Support Project-Based Learning (PjBL) - Sujana, I Made; Saputra, Agus; Fitriana, Eka; Munandar, La Ode Alfin Haris; Izzah, Amniyatul (Journal of English Education Forum (JEEF), 2025)
Pharmacy students require tailored English language skills to support their academic and professional needs. Traditional approaches often fail to address diverse learning preferences, technological advancements, and specific linguistic demands. This study aimed to develop an innovative blended English language learning module using the Whole-Part-Whole (WPW) model to support Project-Based Learning (PjBL) for Pharmacy students at the University of Mataram. Employing a Research and Development (R&D) approach, this study utilized the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). Data were collected through document reviews, FGDs, interviews, observations, and questionnaires and analyzed using quantitative and qualitative methods based on Miles and Huberman's model. The module design successfully integrated ESP, TPACK principles, Blended Learning, WPW structure, and PjBL strategy. Students reported improved engagement, confidence in English use, and collaborative skills. Experts’ evaluations also confirmed the module’s effectiveness. The WPW-based blended English module supports Pharmacy students’ diverse learning needs and enhances language proficiency, collaboration, and 21st-century skills. Future research should expand its application to other disciplines and update digital content continually.